Long‐term mortality associated with acute kidney injury in children following congenital cardiac surgery. Issue 9 (14th May 2014) - Watkins, Scott C.; Williamson, Kelly; Davidson, Mario; Donahue, Brian S.; Hammer, Greg
Summary Objective Children undergoing congenital cardiac surgery (CCS) are at increased risk for acute kidney injury (AKI) due to a number of factors. Recent evidence suggests AKI may influence mortality beyond the immediate postoperative period and hospitalization. We sought to determine the association between renal failure and longer‐term mortality in children following CCS. Methods Our Study population included all patients that underwent cardiac surgery at our institution during a period of 3 years from 2004 through 2006. The primary definition of acute renal injury was based on pRIFLE using estimated creatinine clearance (pRIFLE eCCL). Results Predictors of mortality. Age, single ventricle status, and renal failure as defined by pRIFLE stage F were associated with mortality. The hazard ratio for a patient with renal failure as defined by pRIFLE stage F was 3.82 (CI 1.89–7.75). Predictors of AKI as defined by pRIFLE. Duration of cardiopulmonary bypass (CPB) and age were the only variables associated with pRIFLE by univariate analysis. However, in the ordinal or survival model, age was the only variable associated with renal failure as defined by pRIFLE. As patient age increases from 0.30 to 3.5 years, the risks of having renal injury (pRIFLE stage I) or failure (pRIFLE stage F) decreases (OR 0.44, CI 0.21–0.94). Conclusion Mortality risk following CCS is increased in younger patients and those experiencing postoperative renal failure as defined by pRIFLE for a period of time that extends well beyond the immediate postoperative period and the time of hospitalization.